Examination of the Classroom Management Profiles of Secondary and Primary School Teachers - Beyleroglu, Malik; BezcÄ±, Sakir; Hazar, Muhsin; TÄ±ngaz, Emre Ozan; Baydar, Hacer Ozge (European Scientific Journal, ESJ, 2017)
The aim of this study is to examine the Classroom management profiles of secondary education teachers, including physical education and sport teachers, and elementary teachers. By using a purposeful sampling method in various regions in Turkey, primary school teachers (n=81) and secondary school teachers (n=100) working in Ankara and Gaziantep province constitute the study group. Classroom Management Profile Inventory was used as the operational data collection tool. There was no statistically significant difference between the scores obtained from the general and sub-dimensions of the classroom management profile inventory when there was a comparison between primary school teachers and secondary school teachers. Neither the secondary school nor elementary teachers’ scores on the sub-dimensions and sums of the classroom management profile inventory differ according to branch, age, and sex. However, it was found that the primary school teachers differ in the laissezfaire classroom management profiles according to the placement year. In this sub-dimension, the lowest score belongs to the group "4 years and below", while the highest score belongs to the group "5-7 years". Besides, there was no statistically significant difference on secondary school teachers’ scores on the sub-dimensions and sums of the classroom management profile inventory according to placement year.